2010
DOI: 10.1017/s0029665110001801
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of adipokine secretion byn-3 fatty acids

Abstract: Obesity leads to several chronic morbidities including type 2 diabetes, dyslipidaemia, atherosclerosis and hypertension, which are major components of the metabolic syndrome. White adipose tissue (WAT) metabolism and WAT-derived factors (fatty acids and adipokines) play an important role in the development of these metabolic disturbances. In fact, dysregulated adipokine secretion from the expanded WAT of obese individuals contributes to the development of systemic low-grade inflammation, insulin resistance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 125 publications
5
49
0
5
Order By: Relevance
“…Also in this case our results are in contrast with Simão et al that reported an increase of insulin resistance with n-3 PUFA, but in line with Thorseng et al [44] and Huang et al [45] that suggested that some types of n-3 PUFA may have a protective effect against insulin resistance. Also a review conducted by Moreno-Aliaga et al [46] reached the same results, concluding that the ability of n-3 PUFA to improve obesity and insulin resistance conditions partially results from the modulation of white adipose tissue metabolism and the secretion of bioactive adipokines including leptin, ADN, and visfatin. Analyzing the situation after the OFL, in the group treated with n-3 PUFA there was a better improvement of all parameters peaks, include the insulin resistance biomarkers, after the 6 months treatment, while there was a neutral effect with placebo.…”
Section: Discussionmentioning
confidence: 68%
“…Also in this case our results are in contrast with Simão et al that reported an increase of insulin resistance with n-3 PUFA, but in line with Thorseng et al [44] and Huang et al [45] that suggested that some types of n-3 PUFA may have a protective effect against insulin resistance. Also a review conducted by Moreno-Aliaga et al [46] reached the same results, concluding that the ability of n-3 PUFA to improve obesity and insulin resistance conditions partially results from the modulation of white adipose tissue metabolism and the secretion of bioactive adipokines including leptin, ADN, and visfatin. Analyzing the situation after the OFL, in the group treated with n-3 PUFA there was a better improvement of all parameters peaks, include the insulin resistance biomarkers, after the 6 months treatment, while there was a neutral effect with placebo.…”
Section: Discussionmentioning
confidence: 68%
“…These hypertrophied adipocytes present an altered secretory pattern resulting in increased secretion of proinflammatoryadipokines, cytokines and chemokines such asmonocyte chemoattractant protein-1 (MCP-1), leptin, interleukin (IL)-6 or tumor necrosis factor (TNF)-α, and reduced production of anti-inflammatory adipokines, including adiponectin [14,15].…”
Section: Obesity and Inflammationmentioning
confidence: 99%
“…A significant number of studies consider that n-3PUFAs are able to improve impaired metabolism in obesity by modulating main metabolic pathways in key metabolic organs such as adipose tissue, liver and skeletal muscle [71,38,72,73,46,15,31].Here, we will focus in reviewing theactions and mechanisms of marine origin n-3 PUFAs in adipose tissue metabolism and functions.…”
Section: N-3 Pufas Actions In Adipose Tissuementioning
confidence: 99%
“…Additionally, PUFAs can regulate adipokine expression and secretion by adipose tissue, i.e. EPA has been shown to both up-and down-regulate leptin expression but clearly up-regulates adiponectin expression in adipocytes in culture [9]. In turn, adipokines with proinflammatory (TNF-a, leptin) or anti-inflammatory (IL-10, adiponectin) activities can modify lymph node cell activation or survival [10].…”
Section: Introductionmentioning
confidence: 99%